2022
DOI: 10.14444/8212
|View full text |Cite
|
Sign up to set email alerts
|

How Do Patients With Predominant Neck Pain Improve After Anterior Cervical Discectomy and Fusion for Cervical Radiculopathy?

Abstract: Background: the presence of predominant pain in the arm vs the neck as a predictor of postoperative outcomes after anterior cervical discectomy and fusion (aCDF) has been seldom reported; therefore, the purpose of this study was to determine whether patients with predominant neck pain improve after surgery compared to patients with predominant arm pain or those with mixed symptoms in patients undergoing aCDF for radiculopathy.Methods: a retrospective cohort study was conducted on patients who underwent aCDF at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…A study by Moorthy et al 40 reported that rotator cuff repair in patients with concomitant cervical radiculopathy demonstrated no difference in pain and functional shoulder outcome scores when compared with results from rotator cuff repair in patients without cervical radiculopathy. Anterior cervical discectomy and fusion (ACDF) is an effective procedure for improving neck and arm pain in patients with cervical radiculopathy 41,42 . However, residual shoulder pain in ACDF patients is not uncommon and often suggests concurrent shoulder pathologies 43 .…”
Section: Anatomymentioning
confidence: 99%
“…A study by Moorthy et al 40 reported that rotator cuff repair in patients with concomitant cervical radiculopathy demonstrated no difference in pain and functional shoulder outcome scores when compared with results from rotator cuff repair in patients without cervical radiculopathy. Anterior cervical discectomy and fusion (ACDF) is an effective procedure for improving neck and arm pain in patients with cervical radiculopathy 41,42 . However, residual shoulder pain in ACDF patients is not uncommon and often suggests concurrent shoulder pathologies 43 .…”
Section: Anatomymentioning
confidence: 99%